Tanggapan Guru terhadap Perpustakaan Sekolah di SMA Negeri 1 Lembah Gumanti Kabupaten Solok Sumatera Barat - A.P., Retno Ajeng; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractWriting this paper discusses the teacher's response to the library of public high school 1 Lembah Gumanti. The purpose of writing this paper is to describe the teacher's response to the library of public high school 1 lembah gumanti, Solok Regency, West Sumatra. This research uses a descriptive method with a quantitative approach, which is collecting data directly by distributing questionnaires to respondents in the library of public high school 1 Lembah Gumanti, Solok Regency, West Sumatra. Base on the analysis of the data can be concluded as follows. As many as 67% of teachers in public high school 1 Lembah Gumanti gave positive responses to the library of public high school 1 Lembah Gumanti. In this case it means that the library of public high school 1 Lembah Gumanti is classified as good. This can be seen in the complete library collection, services provided by satisfying librarians and good library management so students are interested in visiting the library. As many as 33% of teachers gave negative responses to the library of public high school 1 Lembah Gumanti. This can be seen from the promotion of the library which is still not maximized, awareness-raising activities in students undertaken by the library are still lacking, and the use of national holidays by the library which is still rarely done as a means to foster student interest in reading.Keywords: responses,Â school,Â libraryÂ